Study of a Dye-Assisted Diode Laser System for Ablation of Dental Caries - AL-DAHAN, Z. T. (Nahrain University College of Engineering Journal, 2009)
In this work, a continuous wave semiconductor diode laser (GaAlAs) which emits radiation at 810 nm and power of 2W maximum was used to ablate caries enamel and dentine from extracted human teeth in conjunction with specialized diode laser absorbing dye indocyanine green . This technique offers selective ablation with minimal risk of thermal damage to surrounding dental tissues because the uptake of the dye and its irradiation by the diode laser together control the ablation